Potensi Inovasi Indonesia di Tengah Bonus Demografi: Menjawab Tantangan Global - Syakirul Niam; Betty Silfia Ayu Utami (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Indonesia’s demographic bonus, marked by a large working-age population, offers significant potential to drive economic growth and innovation. However, despite this demographic advantage, Indonesia faces challenges in workforce quality, investment in research and development (R&D), and technological infrastructure. According to the Global Innovation Index 2023, Indonesia ranks 62nd out of 132 countries in innovation. The low proportion of skilled workers and the lack of formal training programs within companies exacerbate the innovation gap. To fully leverage its demographic potential, Indonesia needs comprehensive policy reforms in education and R&D, increased investment in human capital, and strengthened technological infrastructure. Without these improvements, the demographic bonus risks turning into a long-term burden rather than a catalyst for innovation and economic growth.